Analisis Home Industri Tahu Pletok Karangmoncol Kecamatan Randudongkal Kabupaten Pemalang - Ainun, Salsabila; Tegar Rastiawan, Agung; Purnama, Aji; Dwi Rahayu, Leksani; Mudzakir, Salsabila (KUBIS, 2023)
The purpose of this study was to determine the performance, industrial structure, industry players of the Karangmoncol tofu pletok home industry business. Tofu pletok is a typical food from Karangmoncol Village, Kec. Randudongkal, Kab. Malang. Tofu pletok is different from the usual tofu. In addition, this pletok tofu has a different taste from its competitors. The researched pletok tofu has also been established for 30 years. At the beginning of the establishment of this business, 15 kg of soybean raw materials were needed, until now it has reached 2.5 quintals in a day. This research uses descriptive qualitative research. This study uses 1 sample as a resource, namely the owner of this pletok tofu business. Sources of data used are primary data and secondary data. Data collection techniques through observation or direct observation, interviews, and documentation.